2015
DOI: 10.1007/s00246-015-1265-7
|View full text |Cite
|
Sign up to set email alerts
|

High Overweight and Obesity in Fontan Patients: A 20-Year History

Abstract: Background: The prevalence of obesity in long-term survivors with complex congenital heart disease may be increasing, and little is known about the timing and onset of weight gain and growth patterns in these high-risk patients. Methods and Results: Prevalence rates of overweight/obesity and longitudinal changes in body mass index (BMI) with age were determined in 606 patients with Fontan circulation seen at a tertiary care cardiology center from 1992 – 2012. The number of clinic encounters (n) was stratifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…A study carried out in Fortaleza, Brazil, 21 agrees with the results found in this study, by stating that systolic BP rises concomitantly with increasing age. In relation to the nutritional status, there is an association between the systolic and the diastolic BP 22 and between the diastolic BP and weight, 23 in agreement with the findings. Regarding ethnicity/ race, indigenous individuals showed the highest mean systolic BP; a study that analyzed racial differences and childhood SAH identified higher values in nonHispanic blacks.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A study carried out in Fortaleza, Brazil, 21 agrees with the results found in this study, by stating that systolic BP rises concomitantly with increasing age. In relation to the nutritional status, there is an association between the systolic and the diastolic BP 22 and between the diastolic BP and weight, 23 in agreement with the findings. Regarding ethnicity/ race, indigenous individuals showed the highest mean systolic BP; a study that analyzed racial differences and childhood SAH identified higher values in nonHispanic blacks.…”
Section: Discussionsupporting
confidence: 85%
“…30 The fact that obese individuals have a higher prevalence of elevated BP corroborates studies in Brazil and worldwide that reinforce the existence of a definite association between overweight, obesity and SAH. 7,22,34 The chance of an obese individual to also have SAH is 7.53-fold higher than that of an overweight individual. 35 Mavrakanas et al 36 state that obese children have five to six-fold higher BP than non-obese children.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with several previously published studies carried out worldwide. [21202426] Moreover, Mavrakanas et al ., 2009, observed that obese children had a 5–6-fold higher risk of hypertension than normal children. [27] Obese children might also become victims of bullying, which ultimately results in low self-esteem, anxiety, and shyness, and stress,[20] causing such chronic medical conditions as hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The most recent data showed that one-quarter of ACHD patients were obese, and ACHD patients are at equal risk as their matched peers to be overweight and obese independently of the severity of the lesion. [8][9][10] The most recent data showed that one-quarter of ACHD patients were obese, and ACHD patients are at equal risk as their matched peers to be overweight and obese independently of the severity of the lesion.…”
Section: Overweight/obesity and Underweight In Achd Patientsmentioning
confidence: 99%